Anxiety as a Barrier to Information Processing in the Event of a Cyberattack. Issue 3 (26th March 2015) - Cheung‐Blunden, Violet; Ju, Jiarun
Abstract : As postindustrial societies become more dependent on technology, they also become encumbered by greater risk. With the mounting news reports of cyberattacks, a common reaction to these technology‐based hazards is anxiety. Whether anxiety enhances or erodes information processing is a topic of debate in previous literature, and equally uncertain is whether mass anxiety facilitates or hobbles the public's ability to contemplate current events. In light of three theoretical models in the basic research of anxiety, we hypothesized that (1) anxious participants are less able to recall the information in a news report of cyberattack than their nonanxious counterparts, (2) they become increasingly inept at recalling the details as the storyline unfolds, and (3) this impairment is unique to anxiety. Participants in Study 1 (130 college students) and Study 2 (392 American adults) viewed a news story of a cyberattack and then reported their emotional states and their levels of understanding of the various parts of the report—except that the anxiety in Study 1 was naturalistic, and in Study 2, experimentally manipulated. Results from both studies showed that anxiety undermined recall performance. In addition, Study 1 found that the recall was worse towards the middle and the end of the news story and that other emotions were not significantly associated with memory deficit. Anxiety is discussed as a barrier for the public to stay informed about cyberattacks.